Biomarkers for diagnosis of Pediatric Acute Neuropsychiatric Syndrome (PANS) – Sensitivity and specificity of the Cunningham Panel - Hesselmark, Eva; Bejerot, Susanne (Journal of neuroimmunology, 2017)
Pediatric Acute Neuropsychiatric Syndrome (PANS) and pediatric autoimmune neuropsychiatric disorders associated with streptococcal infections (PANDAS) are conditions marked by sudden onset of obsessive-compulsive disorder (OCD), tics, or avoidant/restrictive food intake in combination with multiple psychiatric symptoms. A diagnosis of PANS or PANDAS may be supported by the Cunningham Panel, a commercially available set of immunologic assays currently in clinical use. However, the relationship between Cunningham Panel results and patient symptoms remains unclear. This study was done to assess the diagnostic accuracy of the Cunningham Panel in patients with suspected PANS or PANDAS. All Swedish patients who had taken the Cunningham Panel prior to June 2014 (n=154) were invited and 53 patients participated in the study. Based on comprehensive psychiatric assessment (the reference standard of diagnosis), subjects were classified as PANS, PANDAS, or neither. Prior Cunningham Panel test results were collected from patient records, and new blood samples were similarly analyzed within the scope of this study. In addition, results were compared to healthy controls (n=21) and a test-retest reliability analysis was performed. Sensitivities of individual biomarkers in the Cunningham Panel ranged from 15 to 60%, and specificities from 28 to 92%. Positive predictive values ranged from 17 to 40%, and negative predictive values from 44 to 74%. A majority of the healthy controls had pathological Cunningham Panel results and test-retest reliability proved insufficient. Clinical use of the Cunningham Panel in diagnosing PANS or PANDAS is not supported by this study. [Display omitted] •PANS and PANDAS are proposed autoimmune disorders with psychiatric presentation.•The Cunningham Panel is currently marketed as a diagnostic tool for PANS and PANDAS.•This is the first study to present diagnostic accuracy data on the Cunningham Panel.•Results offer no support for clinical use of the Cunningham Panel.•The Cunningham Panel may have been prematurely introduced to the clinic.